Evaluation of the effects of donepezil, memantine and α-lipoic acid combined administration in amnesia rats on impaired cognitive functions in terms of behavioural, apoptotic, cholinergic and glutamatergic systems - ÖZBEYLİ, DİLEK (My University, 2021)
Objective: The aim of the study was to evaluate the possible protective effect of donepezil, memantine and alpha-lipoic acid (α-LA) combined therapy in the scopolamine-induced amnesia rat model. Methods: In this study, the effect of combined therapy used in the treatment of scopolamine-induced amnesia on behavioural parameters was evaluated using Y-maze and new object recognition (NOR) test. In addition, muscarinic acetylcholine receptor subtype M1, N-methyl-Daspartate receptor NR2B subunit, brain-derived neurotrophic factor (BDNF) and mitochondrial apoptosis-related proteins [B-cell lymphoma-2 (Bcl-2) / Bcl-2 associated X (Bax) ratio, caspase (casp) – 3, and – 9] expression levels were evaluated using the western blot method in the frontal cortex and hippocampus regions. Results: The main findings of this study demonstrated that in scopolamine-induced amnesia rats, cognitive dysfunction determined by both the Y-maze and the NOR test were reversed with the combined treatment of memantine, donepezil and α-LA. According to immunoblotting results in both brain regions, scopolamine-induced decreased M1, BDNF, Bcl-2 / Bax ratio and increased NR2B, casp-3 and – 9 expression levels were found to be reversed to almost control values with combined treatment. Conclusion: Consistent with the literature, our study results suggest that the positive contribution of α-LA to the combined treatment of donepezil and memantine, which is used in the routine treatment of neurodegenerative diseases, may be a treatment option in the future.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); İncelemeler ve Referanslar (tıbbi); Araştırma ve Teori; Reviews and References (medical); Research and Theory; Alpha-lipoic acid; amnesia; apoptosis; scopolamine; Y-maze; INDUCED MEMORY IMPAIRMENT; NEUROTROPHIC FACTOR; MUSCARINIC RECEPTORS; OXIDATIVE STRESS; SUBTYPES; MODEL; INFLAMMATION; ANTIOXIDANT; HIPPOCAMPUS; MECHANISMS; Alpha-lipoic acid; amnesia; apoptosis; scopolamine; Y-maze